Pengaruh Media Wayang berbasis Cerita Rakyat Sasak terhadap Keterampilan Berbicara Siswa Kelas IV SDN 2 Lembar Selatan - Sopani, Elza Maulia; Zain, Moh. Irawan; Hasnawati, Hasnawati (Universitas Nusantara PGRI Kediri, 2025)
Students' speaking skills can be improved through Sasak folklore-based puppet learning media, making it easier for students to understand concepts and express opinions. The purpose of the study was to determine the effect of Sasak folklore-based puppet media on the speaking skills of fourth-grade students of SDN 2 Lembar Selatan. This study used quantitative research with a Quasi Experimental research type with Nonequivalent Control Group Design. The population was 46 students consisting of two classes, namely class IV-A and IV-B. The sample selection used a saturated sample technique where class IV-A consisted of 24 students as an experiment and class IV-B consisted of 22 students as a control. Data collection techniques were in the form of observation and speaking skills tests. Data from observations of the implementation of puppet media using the Problem Based Learning model obtained an average of 80% with good categories from both teacher and student activities. Test result data were used to test the hypothesis using the t-test. Before implementing the t-test, a prerequisite test was first carried out which included a normality test and a homogeneity test. The results of the pretest normality test for the experiment were sig. 0.163> 0.05 and the control value was sig. 0.071>0.05 while the posttest experiment sig. value is 0.197>0.05 and the control sig. value is 0.272>0.05. The results of the pretest homogeneity test sig. value 0.061>0.05 and the posttest sig. value 0.913>0.05, then the data is said to be homogeneous. The test result data for the hypothesis test using the t test obtained a calculated value of 6.597>table 2.021 and sig. 0.00 <0.05, meaning that the proposed t was rejected and t was accepted, indicating that there was a difference between the two classes after being given treatment, so it was concluded that there was an influence of Sasak folklore-based puppet media on the speaking skills of fourth-grade students of SDN 2 Lembar Selatan.